2015
DOI: 10.4238/2015.october.26.13
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile of a Malaysian Bajau family with familial mitochondrial neurogastrointestinal encephalomyopathy

Abstract: ABSTRACT. Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a rare, autosomal recessive disorder associated with mutations in the thymidine phosphorylase (TYMP) gene. The main objective of this study was to characterize the genetic profiles of the deceased proband's family members (N = 4) using DNA sequencing and to determine miRNA deregulation in MNGIE using miRNA microarray profiling and bioinformatic analysis. We found that the genetic profile of the younger sister showed similar TYMP gene mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In this study we reported a significant dysregulation of 82 miRNAs in the serum of patients compared to age and sex matched healthy controls, however, a critical limitation of this study was the small number of patients recruited (n =5). Previous to this feasibility study, Yong et al reported a miRNA profiling study in a single patient with MNGIE and a cohort of heterozygous family members, using a microarray-based screening [36].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we reported a significant dysregulation of 82 miRNAs in the serum of patients compared to age and sex matched healthy controls, however, a critical limitation of this study was the small number of patients recruited (n =5). Previous to this feasibility study, Yong et al reported a miRNA profiling study in a single patient with MNGIE and a cohort of heterozygous family members, using a microarray-based screening [36].…”
Section: Discussionmentioning
confidence: 99%
“…The only other study which has investigated the involvement of miRNAs in MNGIE is that of Yong et al [29] (2015) who conducted a miRNA expression profile in whole blood of a single patient with MNGIE and a cohort of heterozygous family members [29]. However, no quality control checks were conducted to assess haemolysis, which has been shown to alter miRNA profiles [30].…”
Section: Discussionmentioning
confidence: 99%
“…Onset is usually between the irst and ifth decade in about 60% of individuals and symptoms begin before 20 years. The diagnosis of MNGIE disease can be established in a proband by detection of one of the following: biallelic pathogenic variants in TYMP; markedly reduced levels of thymidine phosphorylase enzyme activity; and elevated plasma concentrations of thymidine and deoxy-uridine [35][36][37][38]. h) TK2-related mtDNA depletion syndrome: Mitochondrial myopathy with mtDNA depletion is caused by pathogenic variants in TK2.…”
Section: G) Mitochondrial Neuro-gastrointestinal Encephalopathy (Mngie)mentioning
confidence: 99%